The effect of the discovery learning model assisted by flipbook media on student learning outcomes in plantae topic - Fitriyana, Fitriyana; Ningsih, Kurnia; Yeni, Laili Fitri (Assimilation: Indonesian Journal of Biology Education, 2025)
In the tenth-grade students of SMA Negeri 4 Pontianak, this study aims to measure the effectiveness of the Discovery Learning model using a Flipbook in enhancing the understanding of the Plantae material. The study adopts a quasi-experimental design with a non-equivalent control group design. Two entire classes were selected as the research sample: Class X MIA 2 as the experimental group receiving the treatment and Class X MIA 4 as the control group without treatment for comparison. The research instrument consisted of a multiple-choice test with a total of 20 items. The comparison of the average scores between the experimental group (15.89) and the control group (15.17) indicates a significant improvement in the experimental group. However, statistical analysis using the Mann-Whitney U test shows no statistically significant difference between the two learning groups. The 13.68% improvement in students' learning outcomes on the Plantae material can be attributed to the implementation of the learning model used in this study.